PWE-002 The Positive Predictive Value Of A Colonoscopist Labelling A Lesion As Cancer – What Should We Tell The Patient?. (9th June 2014) - Verma, AM; Smith, RE; Dixon, A; Chilton, AP
Abstract : Introduction: Colonoscopy is the modality of choice for bowel cancer screening and investigation of iron deficiency anaemia. Hence colonoscopists are most likely to diagnose colorectal cancer (CRC). It is desirable to inform a patient post endoscopy they have CRC but a colonoscopist may fear giving an incorrect diagnosis. All patients with CRC are discussed at the weekly multi-disciplinary team meeting. A delay in treatment is often caused by the patient not being aware of a CRC diagnosis. This may require an additional appointment to inform the patient before the appointment with a Surgeon or Oncologist to discuss treatment. This delay can increase the risk of progression of CRC and reduces the time the patient and family have to adjust to a CRC diagnosis and its consequences. We aim to test the positive predictive value (PPV) of colonoscopists diagnosing CRC and audit if patients were informed. Methods: 8561 colonoscopies undertaken at Kettering General Hospital (KGH), if "tumour/cancer" was recorded this was correlated to outcome. The reporting software gives an option to record if patient "informed of cancer" or "informed of lesion". Results: "Tumour/cancer" recorded 350 times (4.09% of colonoscopies) Confirmed CRC = 333, PPV = 95.14% Adenomas = 12 (3.43%): 7 required surgery, 1 EMR Benign lesions = 5 (1.43%): 2 required surgery 223 of 350 (63.71% ) informed of CRC: 219 had CRC, 4 had adenomas 102 (29.14%) informed of "lesion": 90 had CRC, 12 had benign disease 25 (7.14%) no record (of discussion with patient): 24 had CRC, 1 had adenoma Consultant colonoscopists (241 records) PPV 95.44% 166 out of 241 (68.18%) informed of CRC: 163 had CRC, 3 had adenoma 58 (24.07%) informed of "lesion": 50 had CRC, 3 had adenoma, 5 had benign disease 17 (7.05%) no record: 17 had CRC Trainee colonoscopists (81 records) PPV 92.59% 47 out of 81 (58.02%) informed of CRC: 46 had CRC, 1 had adenoma 26 (32.10%) informed of "lesion": 22 had cancer, 4 had adenoma 8 (9.88%) no record: 7 had CRC, 1 had adenoma Nurse colonoscopists (28 records) PPV 100% 10 out of 28 (35.71%) informed of CRC, 18 out of 28 (64.29%) informed of "lesion" Conclusion: This data shows that colonoscopists are proficient at diagnosing CRC (PPV 95.14%). Those cases not confirmed with CRC usually have serious pathology which often requires surgery (9 out of 17). Yet only 63.71% of patients were informed of CRC. Consultants informed 68.18%, trainees informed 58.02% and nurses informed only 35.71%. To reduce delay in CRC treatment and to give patients more time to deal with CRC diagnosis, colonoscopists should inform patients of a suspicion of CRC (and not a "lesion") and record this on reports. Disclosure of Interest: None Declared.